Struvite and hydroxyapatite recovery from wastewater treatment plant at Autónoma de Occidente University, Colombia (2022)
A study for recovering struvite and hydroxyapatite from wastewater produced on the campus of the Autonoma de Occidente University was conducted, as an option to nutrients recovery. The experiments were carried out using magnesium chloride as precipitation reagent, at pH between 8,0 and 12,8 units for raw wastewater (RW), and between 8,8 and 13,2 units for treated wastewater (TW). A sludge with crystalline structures with dendritic, cruciform and rod morphologies associated with struvite was obtained; although amorphous particles associated with hydroxyapatite and other apatites that can be formed during the processes. In order to guarantee the predominance of struvite and hydroxyapatite over others salts that could be formed, it is necessary to adjust the molar fractions of Mg2+: PO4 3− : NH4 + and Ca2+: PO4 3− , which for the case under study were conditioned by the availability of phosphates in the wastewater.